PELATIHAN PMT (PEMBUATAN MAKANAN TAMBAHAN) BERBASIS PANGAN LOKAL DI DESA BLANG BAROE NAGAN RAYA ACEH - Safrida, Safrida; Syam, Nasrianti; Maisyaroh Fitri Siregar, Siti; Duana, Maiza; Maliza, Noer Octaviana (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2024)
The most common problem of malnutrition occurs in toddlers, including the risk of increased infection, stunting, wasting, and underweight. One step to overcome this problem is through interventions to fulfill toddler nutrition with training in Making Supplementary Food (MSF). This community service activity was carried out in Blang Baro Village, Nagan Raya Regency, Aceh, and involved cadres, midwives, and mothers of toddlers. The method used is the CRP (Community Rural Participatory) approach, which includes the stages of assessment, planning, and implementation of activities. This approach emphasizes empowerment and active participation of participants as the primary strategy. The main ingredients for making MSF, such as mackerel, corn, and green beans, are obtained from traditional markets in Nagan Raya. This activity teaches participants to make MSF products like fish dimsum and green bean corn pudding. The activity results showed that all participants learned how to make the designed MSF products and gained knowledge about selecting nutritious local food ingredients, correct processing techniques, and the importance of fulfilling toddler nutritional needs to support optimal growth and development. However, efforts are needed to increase the diversification of MSF products based on other local foods to increase the attractiveness and variety of consumption for toddlers.